Iraq Public Expenditure and Institutional Assessment, Volume 1 : Public Financial Management in a Conflict-Affected Environment - World Bank (Washington, DC, 2017)
The public expenditure and institutional assessment (PEIA) were motivated by a number of factors. First, both the Government of Iraq (GoI) and its international development partners have recognized the critical importance of sound management of Iraq's substantial public financial resources. Both parties support the reform and modernization of public financial management (PFM), as articulated in the International Compact for Iraq (ICI). Secondly, international experience demonstrates the importance of establishing a baseline against which progress in PFM over time can be measured. This implies the need for an assessment which provides the information necessary to measure the performance of a country's PFM system. Thirdly, the devastating circumstances in Iraq during the past 5 years have made the institutional arrangements for PFM the subject of considerable uncertainty. The PEIA can help to shape and prioritize the necessary development program. The report is organized in two main parts. Volume one contains a summary of the main issues to emerge from the public expenditure and financial accountability (PEFA) assessment and a discussion of a number of specific PFM issues of current importance to Iraq, including: capital investment budgeting (CIB), oil revenue management, the Iraq financial management information system (IFMIS), public accounting and accountability, and payroll management. Volume two contains a detailed technical analysis behind the PEFA assessment.